Chord-based Resource Identifier-to-Locator Mapping and Searching for the Future Internet - Huanlin Liu; Hongyue Dai; Shuaiyong Wu; Sheng Huang (Universitas Ahmad Dahlan, 2014)
A great many problems, such as scalability, mapping data searching, high frequency update of mapping data, arise in the future network resource mapping system for its vast data processing need. Future Network Chord (FN Chord), an algorithm based on Chord and aims at solving the resources identity mapping and searching problem, is put forward by taking advantage of the qualities of scalability, rapid searching speed, high searching efficiency and flexible naming of chord in order to solve this problem. What’s more, an extra interest node index table for FN Chord is designed to record the hotspot resource mapping location in the paper. So, the resource searching strategy, which is named as Interest Index Table Future Network Chord (IIT-FN Chord) is proposed to search the resource in the paper. The entropy weight method is used to calculate the node interest level according the interest nodes’ resource item online time and visited times and to renew the interest index table. Moreover, probability replacement method is proposed to replace the outdated item on interest index table with new item. Simulation results show that the algorithm can decrease the average searching latency, average searching hops and thus increases the searching efficiency for the resource searching.